Fatigue strength of Al-Cu cast alloy with different pouring temperature - . Akhyar; P. T. Iswanto; V. Malau; F. V. Putra; A. Farhan (Metalurgija, 2024)
This experiment aimed to evaluate how pouring temperature affects fatigue strength of Al-Cu cast alloy. Subsequently, commercial aluminum ingots, such as Al-2024 were remelted and then machined into samples for both tensile and fatigue testing. These samples were cast at three different temperature of 688, 738, and 788 °C while maintaining a constant mold temperature of 220 °C. The results showed that the highest tensile strength was 201,06 MPa at 738 °C. Additionally, the greatest fatigue strength was observed at 80,4 MPa at pouring temperature of 738 °C. It was observed that variations in pouring temperature can significantly impact fatigue strength of cast alloy. At the highest pouring temperature of 788 °C, the presence of pores in the metal casting samples resulted in a decrease in both tensile and fatigue strength. Furthermore, when examining the surface fractography of casting sample, the presence of brittle cracks in alloy was observed.